Seroprevalence of Q Fever Among the Indigenous People (Orang Asli) of Peninsular Malaysia - Khor, Chee-Sieng; Mohd-Rahim, Nurul-Farhana; Hassan, Habibi; Chandren, Josephine Rebecca; Nore, Siti-Sarah; Johari, Jefree; Loong, Shih-Keng; Abd-Jamil, Juraina; Khoo, Jing-Jing; Lee, Hai-Yen; Pike, Brian L; Wong, Li Ping; et al. (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2018)
Q fever is a disease caused by Coxiella burnetii. It is a disease of public health concern in many parts of the world. In this study, we described the seroprevalence of Q fever among selected populations of Orang Asli (OA), indigenous people, many of whom live within the forest fringe areas of Peninsular Malaysia. Serum samples were obtained from 887 OA participants from selected villages. Samples were analyzed for the presence of IgG antibodies reactive against C. burnetii by enzyme-linked immunosorbent assay. Statistical methods were used to identify possible associations between seropositivity for C. burnetii and a number of demographic variables obtained from the questionnaires. In total, 9.6% (n = 85/887) of the serum samples were reactive to C. burnetii. Statistical results suggest that elderly male OA residing in OA village, Bukit Payung, were most likely to be tested seropositive for C. burnetii. This study suggests that OA are at a significant risk of contracting C. burnetii infection, and both demographic and geographic factors are important contributors to this risk. Further prospective studies are needed to establish the true burden of C. burnetii infection within the indigenous population as well as within Peninsular Malaysia as a whole.